Sensing of ozone (O3) molecule via pristine singe-walled aluminum nitride nanotube: A DFT study. (January 2016) - Kamalinahad, Saeedeh; Solimannejad, Mohammad; Shakerzadeh, Ehsan
Abstract: Adsorption of O3 molecule on the surface of zigzag [5, 0] single-walled AlNNT is investigated using DFT calculation for investigating their potential use as nanosensors. The O3 is favorably chemisorbed on the AlNNT, with adsorption energy in the range −0.60 to −1.88 eV at B3LYP/6-31G* level. The adsorption of O3 molecule onto the AlNNT would influence the electronic conductance and mechanical properties, which could use as a signal of gas sensor. It was found that this sensor has a high sensitivity by reducing Eg from 4.16 eV in the pristine tube to 0.87 eV in the C configuration. Also this sensor has short recovery time due to the adsorption energy of O3 molecule is not so large. So based on the above results, it is expected that AlNNT can act as a sensor to detect O3 molecule. Highlights: Adsorption of O3 on a single-walled AlNNT was investigated. The electronic conductance properties of AlNNT may be increased upon O3 adsorption. The AlNNT can act as a sensor to detect O3 molecule.